Compulsive Sexual Behavior Online and Non-online in Adult Male Patients and Healthy Controls: Comparison in Sociodemographic, Clinical, and Personality Variables - González-Bueso, Vega; Santamaría, Juan José; Caro-Pérez, Oriol; Fernández, Daniel; Baño-Alcazar, Marta; Jiménez-Murcia, Susana; Håkansson, Anders; del Pino-Gutiérrez, Amparo; Ribas, Joan (Frontiers in Psychiatry, 2022)
Background and aims: Compulsive Sexual Behavior (CSB) is characterized by a persistent pattern of failure to control sexual impulses, resulting in repetitive sexual behavior over a prolonged period that causes marked discomfort in personal, family, social, school, work or in other functional areas. The evolution of the worldwide incidence of this disorder warrants further studies focused on examining the characteristics of the affected people. The purpose of this study was to compare online Compulsive Sexual Behaviour (when the problematic sexual practices were online) and non-online Compulsive Sexual Behaviour (when the problematic sexual practices were in-person) patients (OCSB and non-OCSB, respectively), and healthy controls in terms of sexual behaviour, sociodemographic variables and psychopathology and personality characteristics. Method: A sample of 80 Compulsive Sexual Behaviour male patients consecutively admitted to our Behavioral Addictions Unit and 25 healthy male controls, participated in the study. The CSB group was comprised by 36 online CSB patients (mean age 42.25, SD: 10.0) and 44 non-online CSB patients (mean age 43.5, SD: 11.9). Scores on the Sexual Compulsivity Scale, Temperament and Character Inventory-Revised, Symptom CheckList-90 Items-Revised, State-Trait Anxiety Index and additional demographic, clinical, and social/family variables related to sexual behaviours between the three groups were compared. Results: When compared with healthy controls, both clinical groups showed higher psychopathology in all measures as well as higher harm avoidance and self-transcendence and lower self-directness and cooperativeness. When comparing OCSB and non-OCSB patients, results showed that non-OCSB patients exhibited higher prevalence of sexually transmitted diseases, higher percentage of homosexual and bisexual orientation and higher scores in anxiety and in sexual impulse control failure. Conclusions: Both online and non-online CSB patients may experience a variety of comorbid psychological and medical problems. Patients with non-OCSB may suffer more consequences that are negative. Therefore, these results should be considered when designing the most convenient therapeutic approach. Whether sexual orientation plays a role in treatment needs and treatment response in CSB, should be further explored in future studies.